The interference of EFL student’s native language in students english pronunciation - Riswanto Riswanto (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
The study indicates the interferences occurred by the Kaurnese and Rejangnese students in pronouncing English sounds and the factors that affect pronunciation interference of Kaurnese and Rejangnese students in pronouncing English sounds. The respondents were ten students of the English Education Study Program. They are five Kaurnese students whose L1 is Kaurnese and five Rejangnese students whose L1 is Rejangnese. The researcher applied a qualitative approach and conducted a case study design. The instruments used to collect the data were observation by reading a list of words and interviews about factors affecting students' pronunciation interference. The result of data analysis showed that Kaurnese students had interference in pronouncing 30 sounds while Rejangnese students had interference in pronouncing 22 sounds. The data also showed that three main factors influence students' pronunciation; native language, age, and the difference in language features between English and students' native language. In conclusion, all Kaurnese and Rejangnese students had interference in pronouncing English sounds. Kaurnese language is more interference with English pronunciation than the Rejangnese language. Based on the above context, this study suggests the students practice more English pronunciation and put more attention to the native language interference. The lecturer is expected to be able to help the students to reduce the mispronounced words. The study also suggests that further researchers take special attention to this phenomenon to solve the students' problems with English pronunciation.